Inhibition test of the local anesthetics articaine 4% with adrenaline 1:100000 to the growth of staphylococcus aureus bacteria in vitro - Gostry A. Dohude; Wahyu Ardi (Journal of Dentomaxillofacial Science, 2021)
Objective: This research was conducted to determine the effectiveness of 4% local anesthetic with 1:100000 adrenaline in inhibiting the Stahapylococcus aureus growth. Material dan Methods : The study is true experimental laboratories with posttest-only control group design. This study sample was Articain 4% with 1:100000 adrenaline and Staphylococcus aureus bacteria that were multiplied in Microbiology Laboratory of the Faculty of Pharmacy, University of North Sumatera. The Articain 4% used in this research were obtained from one of dental suppliers in Jakarta. This study used three treatment groups namely Articaine 4%, Amoxicillin (positive control), and Aquades (negative control). Testing the treatment group for the Staphylococcus aureus was carried out using the Kirby-Bauer disk diffusion method with nine repetitions. Results : The result from this research indicate that Articaine 4% with 1:100000 adrenaline can inhibit the growth ofStaphylococcus aureus that can be seen from clear zone at paper discs that have been given Articaine 4%, Amoxicillin (positive control), and Aquadest (negative control). The results also showed a significant difference from diameter of the inhibition zone at each treatment group (p<0,005). Conclusion: Articaine 4% with 1:100000 adrenaline has antibacterial effect that can inhibit the growth of Staphylococcus aureus in oral cavity with in vitro.